Physician judgement in predicting obstructive coronary artery disease and adverse events in chest pain patients. Issue 11 (2nd February 2022) - Fordyce, Christopher B; Hill, C Larry; Mark, Daniel B; Alhanti, Brooke; Pellikka, Patricia A; Hoffmann, Udo; Patel, Manesh R; Douglas, Pamela S
Abstract : Objective: To evaluate informal physician judgement versus pretest probability scores in estimating risk in patients with suspected coronary artery disease (CAD). Methods: We included 4533 patients from the PROMISE (Prospective Multicenter Imaging Study for Evaluation of Chest Pain) trial. Physicians categorised a priori the pretest probability of obstructive CAD (≥70% or ≥50% left main); Diamond-Forrester (D-F) and European Society of Cardiology (ESC) pretest probability estimates were calculated. Agreement was calculated using the κ statistic; logistic regression evaluated estimates of pretest CAD probability and actual CAD (as determined by CT coronary angiography), and clinical outcomes were modelled using Cox proportional hazard models. Results: Physician estimates agreed poorly with D-F (κ 0.16; 95% CI 0.14 to 0.18) and ESC (κ 0.04; 95% CI 0.02 to 0.05). Actual obstructive CAD was significantly more prevalent in both the high-likelihood (OR 3.30; 95% CI 2.30 to 4.74) and the intermediate-likelihood (OR 1.43; 95% CI 1.16 to 1.76) physician-estimated groups versus the low-likelihood group; ESC similarly differentiated between the three groups (OR 9.07; 95% CI 2.87 to 28.70; and OR 3.87; 95% CI 1.22 to 12.28). However, using D-F, only the high-probability group differed (OR 2.49; 95% CI 1.74 to 3.54). Only physician estimates were associated with a higher incidence of adjusted death/myocardial infarction/unstable angina hospitalisation in the high-probability versus low-probability group (HR 2.68; 95% CI 1.52 to 4.74); neither pretest probability score provided prognostic information. Conclusions: Compared with D-F and ESC estimates, physician judgement more accurately identified obstructive CAD and worse patient outcomes. Integrating physician judgement may improve risk prediction for patients with stable chest pain. Trial registration number: NCT01174550 .